A Rocket‐Triggered Lightning Flash Containing Negative‐Positive‐Negative Current Polarity Reversal During Its Initial Stage. Issue 9 (10th May 2021) - Li, Fengquan; Sun, Zhuling; Jiang, Rubin; Tang, Guoying; Liu, Mingyuan; Li, Xiao; Zhang, Hongbo; Yuan, Shanfeng; Tian, Ye; Qie, Xiushu
Abstract: A rocket‐triggered lightning flash containing negative‐positive‐negative current polarity reversal during its initial stage is analyzed using multiple synchronized observation data. The flash was triggered under a thunderstorm transition zone between the convective region and the stratiform region. The upward positive leader branched and developed toward the stratiform region. When the negative initial continuous current was decreasing, a negative stepped leader was transformed from a recoil leader on a preexisting positive branch. As the negative leader developed toward the convective region, a breakdown process initiated on a preexisting positive channel and propagated toward the back end of the negative stepped leader, accompanied with a positive electric field change pulse. The current polarity changed from negative to positive about 0.22 ms after the onset of the breakdown process. The negative leader terminated after propagating for 71.08 ms, while scattered discharges on other positive branches maintained to develop, and then the ICC polarity changed from positive to negative. Key Points: A lightning flash with negative‐positive‐negative current polarity reversal was triggered under the transition zone of a thunderstorm A negative recoil‐stepped leader reconnected to the grounding channel, changing the current polarity to be positive The negative leader terminated while discharges on the positive leaders still developed, changing the current polarity to be negative